The Effect of Dual-Class Share Structures and Insider Ownership on Share Repurchases During Uncertainty: US Evidence - Jabeskog,Edvin; Lundin,Gustav Adam (2025)
Seminar date: 2025-06-03 Course: BUSN79 - Degree Project in Accounting and Finance Authors: Edvin Jabeskog & Gustav Lundin Advisor/Examiner: Elias Bengtsson/Reda Moursli Five key words: Payout Policy, Economic Policy Uncertainty (EPU), Share-Class Structure, Insider Ownership, Corporate Governance. Purpose: The purpose of the paper is to examine the extent to which firms' share-class structure and level of insider ownership affect share repurchase behavior under uncertainty. Methodology: The study applies five different regression models. The dependent variable is share repurchase, measured as repurchase in absolute dollars divided by the market value of equity at the beginning of the quarter. All independent variables are lagged by one quarter to ensure that they precede the share repurchase decision, thereby reducing potential endogeneity. The two main explanatory variables are interaction terms: one between the EPU index and share-class structure, and the other one between the EPU index and the level of insider ownership. Theoretical perspectives: The theoretical framework applied in the study builds on the Agency Theory and the Signaling Theory to explain how firms ownership structure influences share repurchase decisions under uncertainty. Empirical foundation: The empirical foundation consists of a unbalanced panel dataset of 2,384 firms listed on Nasdaq and the New York Stock Exchange, covering the period from Q2 2015 to Q1 2025. This results in a total of 47,596 firm-quarter observations. The data includes firm-level information on share repurchases, ownership structure, and uncertainty indicators such as the EPU index and VIX index. Conclusions: The main finding of this paper is the new evidence showing that higher levels of insider ownership lead to increased share repurchase activity during heightened economic policy uncertainty. These results support the pre-commitment hypothesis. While we do not find any evidence that dual-class firms respond differently to elevated uncertainty compared to single-class firms, our findings highlight the need for further research on corporate governance structures and their role in shaping responses to uncertainty. Particularly, how the gap between cash flow rights and voting rights affects the firms’ decisions during uncertain times.